Teachers’ Perceptions of Literacy Implementation in Elementary Schools - Rahmi, Intan Aulia; Santi, Arfa Novia; Ramadhan, Syahrul; Sukma, Elfia (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2024)
The purpose of this research is to find out how teachers perceive the implementation of literacy at the Gugus 1 Elementary School, North Padang District, Padang City. The research method used is quantitative descriptive. Data collection techniques through distribution of surveys implementing literacy questionnaires. The dimensions of implementing literacy described in this research consist of positive statements and negative statements. The results of the research show that teachers have a fairly positive perception tendency, this can be seen from the percentage of scores obtained from distributing the questionnaire and the explanation from the table. A very positive perception shows that teachers also participate in literacy activities at school. These results come from an analysis of the factors that cause teacher perceptions, namely functional factors and structural factors. Apart from that, it can be said that the teacher has been successful in implementing reading literacy.